Orchestration of tissue‐scale mechanics and fate decisions by polarity signalling. (17th May 2021) - Dias Gomes, Martim; Iden, Sandra
Abstract: Eukaryotic development relies on dynamic cell shape changes and segregation of fate determinants to achieve coordinated compartmentalization at larger scale. Studies in invertebrates have identified polarity programmes essential for morphogenesis; however, less is known about their contribution to adult tissue maintenance. While polarity‐dependent fate decisions in mammals utilize molecular machineries similar to invertebrates, the hierarchies and effectors can differ widely. Recent studies in epithelial systems disclosed an intriguing interplay of polarity proteins, adhesion molecules and mechanochemical pathways in tissue organization. Based on major advances in biophysics, genome editing, high‐resolution imaging and mathematical modelling, the cell polarity field has evolved to a remarkably multidisciplinary ground. Here, we review emerging concepts how polarity and cell fate are coupled, with emphasis on tissue‐scale mechanisms, mechanobiology and mammalian models. Recent findings on the role of polarity signalling for tissue mechanics, micro‐environmental functions and fate choices in health and disease will be summarized. Abstract : This review summarises the recent insights into the interplay of polarity proteins, cell mechanics and fate decisions in development, homeostasis and disease context with a focus on mammalian model systems.